4x-6=2x-6

Simple and best practice solution for 4x-6=2x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-6=2x-6 equation:


Simplifying
4x + -6 = 2x + -6

Reorder the terms:
-6 + 4x = 2x + -6

Reorder the terms:
-6 + 4x = -6 + 2x

Add '6' to each side of the equation.
-6 + 6 + 4x = -6 + 6 + 2x

Combine like terms: -6 + 6 = 0
0 + 4x = -6 + 6 + 2x
4x = -6 + 6 + 2x

Combine like terms: -6 + 6 = 0
4x = 0 + 2x
4x = 2x

Solving
4x = 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
4x + -2x = 2x + -2x

Combine like terms: 4x + -2x = 2x
2x = 2x + -2x

Combine like terms: 2x + -2x = 0
2x = 0

Divide each side by '2'.
x = 0

Simplifying
x = 0

See similar equations:

| 3x+15+3y=x+10 | | b+-2b+-4= | | 21=9+3 | | 3(3x+7)=48 | | 21=9+3x | | (-6p)+(-6p)=-112 | | -14-7x=-8x-8 | | (4x+2)=(6x-30) | | 7a+4m+7= | | 6-x+2=-3 | | Y=21x+98 | | 6-6a=-6-5a+5 | | 7/3x+2/5= | | 2x=77 | | y+.8=.6(y+4) | | 3+2x+5=-17 | | 3(2t+2)= | | y=0.2x^3-5 | | -2xb= | | 2m+9=90 | | f(x)=-4cos(x) | | 6y-16=90 | | f(-x)=7x^2+3x-8 | | 518=vot-16t^2 | | 5x+7=x-17 | | 518=vot-16t | | 6x-(2)=26 | | 5(x-2)=8x-x | | p=4x+450 | | 0.3X-1.8=-5.04 | | -10=3f+2f | | 14+7x-6-15x+5=5x+7-12x+5-12 |

Equations solver categories